2020
DOI: 10.18502/ijph.v49i9.4081
|View full text |Cite
|
Sign up to set email alerts
|

The Unmet Healthcare Needs: Evidence from Serbia

Abstract: Background: We aimed to determine the socio-economic factors associated with unmet healthcare needs of the population aged 20 and over in Serbia. Methods: We used data from the 2013 National Health Survey (NHS) of the population of Serbia. We focused only on the data concerning the population aged 20 and over. The final sample thus included 13,765 participants. The logistic regression was used to examine the socio-economic factors associated with unmet health care needs. Results: According to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The consequences may be the inequities in access to Serbian health care that is observed for particularly vulnerable groups, such as Roma and the people uninsured from the National Health Insurance Fund [ 32 ]. High levels of reported unmet needs among, for instance, women, the elderly, lower educated and those with lower income are seen in Serbia, together with high levels of private out-of-pocket payments [ 71 ]. Correspondingly, the most reported unmet need reported by Serbians were financial reasons, followed by waiting times and distance or transportation difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences may be the inequities in access to Serbian health care that is observed for particularly vulnerable groups, such as Roma and the people uninsured from the National Health Insurance Fund [ 32 ]. High levels of reported unmet needs among, for instance, women, the elderly, lower educated and those with lower income are seen in Serbia, together with high levels of private out-of-pocket payments [ 71 ]. Correspondingly, the most reported unmet need reported by Serbians were financial reasons, followed by waiting times and distance or transportation difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is comparable with a study from Serbia which showed that divorced had the greatest unmet needs even though they had more contact with health services because of their social and emotional problems. 44 …”
Section: Discussionmentioning
confidence: 99%
“…Our study is comparable with a study from Serbia which showed that divorced had the greatest unmet needs even though they had more contact with health services because of their social and emotional problems. 44 Generally, older people with poorer socioeconomic status have been found to have poor access to healthcare particularly those in rural areas of a country. 45 A study in China also indicated that the utilization of healthcare services increased among people living in rural areas.…”
Section: Predisposing Factors Associated With Umet Needs Of Health Se...mentioning
confidence: 99%
“…Research related to the prevalence of unmet health needs in a survey of (around) 13760 citizens of Serbia, conducted by the Ministry of Health of the Republic of Serbia in 2013, showed that the biggest obstacles to meeting the needs of health care in this population group are due to financial reasons (20%), long wait for an appointment with a doctor (8%), and problems with transportation to a remote place where health care is provided (5%). The biggest obstacles in achieving health care relate to dental (13.5%), general health care (13%), prescribing necessary medications (11%), and care for patients with altered and impaired mental health (2.5%) (13). The estimated number of people with unmet health needs in our country indicates that significant changes in health policy are necessary.…”
Section: To the Editormentioning
confidence: 99%
“…Public health policies do not receive the necessary and sufficient social attention. Reducing disparities in health and health care is a crucial precondition for the future evolution of health systems and their institutions (13).…”
Section: To the Editormentioning
confidence: 99%